Downsize : living large in a small house - Koones, Sheri, 1949- (The Taunton Press, Inc., 2019)
"The 25 small houses presented in Downsize are owned by people who have made a conscious decision to downsize from a larger home to a smaller home--or who just decided to build small in the first place. Some of the houses are new (site-built or prefab), others are remodels. All are 2,000 sq. ft. or less. The featured houses show how to use space efficiently through such strategies as: - creative storage space - multi-purpose rooms - pocket and barn doors - integrating smaller appliances"--